The effect of miR-381 on proliferation and prognosis of breast cancer by altering CCNA2 expression - Ming-Gang Cao; Yan Wang; Zhi-Min Yang; Yang Wang; Mei-Qing Wang; Shuai Zhuo; Yan Yang; Chun-Sheng Liu (Taylor & Francis Group, 2024)
Background MiR-381 can regulate the expression of cyclin A2 (CCNA2) to inhibit the proliferation and migration of bladder cancer cells, but whether miR-381 has the same function in breast cancer is not well know.Methods The over express or silence miR-381 expressing cell lines were constructed by lentivirus infection to reveal the biological functions of miR-381 in vitro. The expression of miR-381 and CCNA2 in 162 breast cancer patients were detected to further reveal their impact and predictive value on progression-free survival (PFS) and overall survival (OS).Results After transfection of MDA-MB-231 and MCF-7 cells with miR-381 mimics, the expression of miR-381 was effectively up-regulated and CCNA2 was effectively down-regulated, while the opposite results were observed in tumour cell which transfected with miR-381 inhibitors. After transfection of cell lines with miR-381 mimics, tumour cell activity was significantly reduced, while the opposite results were observed in tumour cell which transfected with miR-381 inhibitors. The area under curves (AUCs) of miRNA-381 and CCNA2 for predicting PFS and OS were 0.711, 0.695, 0.694 and 0.675 respectively. Cox regression analysis showed that miRNA-381 ≥ 1.65 2−ΔΔCt and CCNA ≥ 2.95 2−ΔΔCt were the influence factors of PFS and OS, the hazard ratio (HR) values were 0.553, 2.075, 0.462 and 2.089, respectively.Conclusion miR-381 inhibitors breast cancer cells proliferation and migration by down-regulating the expression of CCNA2, both of them can predict the prognosis of breast cancer.